SISTEM INFORMASI CUSTOMER SERVICE OFFICER TROUBLESHOOTING PADA PT. ADAU PUTRA (Information Technology and Telematics, 2014)
Abstract - Internet is a service that allows its users to communicate between each other and can be accessed anywhere, at any time and by anyone. As an internet service provider company, PT Adau Putra Network tasked to serve customer needs in terms of internet access and networking service. The troubleshooting process is also included in the provision of internet activities. This is done to improve the quality of services provided. This research aims to build a web-based information systems that can be used in assisting the troubleshooting process. Where it covers the process of reporting problems, sets the work list of technician and documenting the activities that have been carried out. The system is built using Dreamweaver and the programming language used is PHP. The database was built using phpMyAdmin which is opensource software database processing. The system is designed in such a way to facilitate clients in problem reporting and related officials to perform troubleshooting on the services. This system is equipped with a notification of incoming complaints and the work list of each technician.   Keywords: Information Systems, Customer Service Officer, Troubleshooting. Abstrak - Internet adalah suatu layanan yang memungkinkan para penggunanya untuk saling berkomunikasi antara satu dengan yang lainnya serta dapat diakses dimana saja, kapan saja dan siapa saja. Sebagai perusahaan penyedia layanan internet, PT. Adau Putra Network bertugas untuk melayani kebutuhan pelanggannya dalam hal akses internet dan layanan jaringan. Selain itu proses troubleshooting juga termasuk dalam kegiatan penyelenggaraan internet. Hal ini dilakukan untuk meningkatkan kualitas layanan yang diberikan. Penelitian ini bertujuan untuk membangun sebuah sistem informasi berbasis web yang dapat digunakan dalam membantu proses troubleshooting. Dimana didalamnya mencakup proses pelaporan masalah, pembagian kerja teknisi serta dokumentasi kegiatan yang telah dilakukan. Sistem ini dibangun dengan menggunakan Dreamweaver dan bahasa pemrograman yang digunakan adalah PHP. Bagian database dibangun dengan menggunakan phpMyAdmin yang merupakan perangkat lunak opensource pengolah database. Sistem ini dirancang sedemikian rupa untuk memudahkan pelanggan dalam pelaporan masalah dan petugas yang terkait dalam melakukan pelayanan troubleshooting. Sistem ini dilengkapi dengan notifikasi terhadap komplain yang masuk serta agenda perbaikan yang dilakukan oleh tiap teknisi.   Kata Kunci : Sistem Informasi, Customer Service Officer, Troubleshooting.